Autoimmune cerebellar hypermetabolism: Report of three cases and literature overview - Brunet de Courssou, J.-B.; Castilla-Lievre, M.A.; Maillot, J.; Brechemier, M.-L.; Ohlmann, C.; Sallansonnet-Froment, M.; Tafani, C.; Psimaras, D.; Ricard, D.; Bompaire, F.; Taifas, I. (Revue neurologique, 2022)
•Autoimmune encephalitis is a classical cause of cerebellar damage in adults.•Cerebellar hypermetabolism on 18F-FDG PET-CT is not specific.•It has been reported in various diseases, including autoimmune encephalitis.•This hypermetabolism could be a diagnostic aid in autoimmune encephalitis.•The vermian predominance of the hypermetabolism may be of interest. We report three cases of vermian cerebellar hypermetabolism in patients with autoimmune encephalitis. One of our patients was positive for anti-Ma2 antibodies and one for anti-Zic4 antibodies while the remaining patient did not present any known antibodies. The seronegative patient deteriorated after immune checkpoint inhibitor treatment for a pulmonary adenocarcinoma and improved with immunosuppressive drugs, which is in favour of an underlying autoimmune mechanism. They all presented with subacute neurological symptoms. Brain magnetic resonance imaging was normal except in one patient, where hyperintensities were present on FLAIR sequence around the third ventricle and the cerebral aqueduct. 18F-FDG brain positron emission tomography with computed tomography (18F-FDG PET-CT) demonstrated an unusual vermian cerebellar hypermetabolism in the three cases. While cerebellar hypermetabolism on 18F-FDG PET-CT has been described in various neurological diseases, such vermian – and more broadly cerebellar – hypermetabolism was seldom described in previous studies on autoimmune encephalitis. When differential diagnoses have been ruled out, this pattern may be of interest for the positive diagnosis of autoimmune encephalitis in difficult diagnostic cases.